Info-rich - info-poor : access and exchange in the global information society - Haywood, Trevor (Bowker Saur LondonGB, 1995)
Analyses the world as an information system. Explores the problems, iniquities, controversies and potential arising from our databased society. Discusses subjects such as deindustrialization and information, copyright and transborder flow.